Observability of YSOs with the WISE and AKARI infrared space observatories. Issue 9 (November 2013) - Zahorecz, S.; Töth, L.V.; Marton, G.; Ueno, M.; Tamura, M.; Kawamura, A.; Kitamura, Y.; Barnaföldi, Gergely Gábor; Forgás‐Dajka, Emese; Kiss, Csaba; Verebélyi, Erika
Abstract Large area surveys allow us to identify young stellar objects and classify them based on their colours. The near‐, mid‐ and far‐infrared filters' sensitivities are different, therefore different proportions of young stars are observable. Evolutionary times for the different classes can be concluded from the popularity of the classes. Our aim was to investigate the completeness of the YSO detections. With the use of only mid‐ or only far‐infrared surveys, we will miss one part of the young stellar objects. Without far‐infrared data one third of the Class 0–II objects can remain invisible. Class III sources are almost invisible above 65 μm. For a comprehensive study we have to use the available data in the whole infrared range. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)